ANALISIS RASIO KEUANGAN PERBANKAN UNTUK MENILAI KINERJA KEUANGAN BANK - Damayanti, Tri; Andriyani, Dini (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
This research aims to find out the financial ratio of PT Bank Negara Indonesia (Persero), Tbk. in 2017 - 2020 and to find out the financial performance of PT Bank Negara Indonesia (Persero), Tbk. in 2017 - 2020 which is reviewed from the aspect of banking financial ratios. Based on the results of the analysis showed that PT Bank Negara Indonesia (Persero), Tbk. In 2017 to 2020, there are variable ratio results that are variable but still within normal numbers. This can explain that PT Bank Negara Indonesia (Persero), Tbk. it has good financial performance judging by liquidity, rentability and solvency ratios. Therefore, PT Bank Negara Indonesia (Persero), Tbk. can improve its financial health and improve its performance to the maximum